Are farmers in the transitional economies likely to benefit from forming collaborative marketing groups? - Murray-Prior, Roy B. (2008)
Trade liberalization has opened up the food market in many transitional economies. This has created an opportunity for smallholder farmers to access higher-value markets, but it has also exposed them to competition from trading partners. Key issues in linking smallholder producers to higher-value markets are overcoming the diseconomies of size, poor infrastructure, lack of market signals for quality, high transaction costs, and the poor quality associated with traditional supply chains. A common suggestion made by many development workers and politicians to overcome these problems is to encourage farmers to form collaborative marketing groups. Furthermore, there is a common misperception that market intermediaries are taking advantage of the farmers and are the primary cause of poor farm-gate prices. Some schemes which aim to help smallholder producers access higher prices (e.g., Fairtrade) insist that farmers be part of a cooperative that delivers the product to market. Unfortunately, there is abundant evidence from the experience of smallholder farmers in the transitional economies that collaborative marketing groups are seldom competitive in either the traditional market or the emerging market. This paper will look at the question of if and under what conditions smallholder farmers in the transitional economies are likely to benefit from forming collaborative marketing groups. It will use evidence from the literature and the author's experiences in researching the success of marketing groups in the Philippines and Papua New Guinea. The main finding is that most are doomed to fail unless key prerequisites exist: a comparative advantage for the group and a sufficient level of social capital and trust in the community. A lack of social capital and trust in PNG and the Philippines means that collaborative structures need to incorporate mechanisms that prevail over this problem.
Keywords: Cooperative; Collaborative marketing groups